New Models for Managing Longevity Risk Public-Private Partnerships - Mitchell, Olivia (Oxford University Press, 2022)
Notwithstanding the terrible price the world has paid in the Coronavirus pandemic, the fact remains that longevity at older ages is likely to continue to rise in the medium and longer term. This volume explores how the private and public sectors can collaborate via public-private partnerships (PPPs) to develop new mechanisms to reduce older people's risk of outliving their assets in later life. As we show in this volume, PPPs typically involve shared government financing alongside private-sector partner expertise, management responsibility, and accountability. In addition to offering empirical evidence on examples where this is working well, our contributors provide case studies, discuss survey results, and examine a variety of different financial and insurance products to better meet the needs of the aging population. The volume will be informative to researchers, plan sponsors, students, and policymakers seeking to enhance retirement plan offerings.